Response of Sesame to Selected Herbicides Applied Early in the Growing Season. (2nd July 2018) - Grichar, W. James; Rose, Jack J.; Dotray, Peter A.; Baughman, Todd A.; Langham, D. Ray; Werner, Kaisa; Bagavathiannan, Muthu
Abstract : Growth chamber experiments were conducted to evaluate the response of sesame to PRE and POST applications of soil residual herbicides. PRE applications of acetochlor and S -metolachlor at 1.26 and 1.43 kg ai·ha −1 showed little or no sesame injury (0 to 1%) 4 wks after herbicide treatments (WAT). POST treatments of acetochlor and trifluralin made 3 wks after planting (WAP) resulted in greater sesame injury (40%) compared to applications at bloom (18%). Field studies were conducted in Texas and Oklahoma during the 2014 and 2015 growing seasons to determine sesame response to clethodim, diuron, fluometuron, ethalfluralin, quizalofop-P, pendimethalin, pyroxasulfone, trifluralin, and trifloxysulfuron-sodium applied 2, 3, or 4 weeks after planting (WAP). Late-season sesame injury with the dinitroaniline herbicides consisted of a proliferation of primary branching at the upper nodes of the sesame plant (in the shape/form of a broom). Ethalfluralin and trifluralin caused more "brooming" effect than pendimethalin. Some yield reductions were noted with the dinitroaniline herbicides. Trifloxysulfuron-sodium caused the greatest injury (up to 97%) and resulted in yield reductions from the untreated check. Early-season diuron injury (leaf chlorosis and necrosis) decreased as application timing was delayed, and late-season injury was virtually nonexistent with only slight chlorosis (<4%) still apparent on the lower leaves. Sesame yield was not consistently affected by the diuron treatments. Fluometuron caused early-season injury (stunting/chlorosis), and a reduction of yield was observed at one location. Pyroxasulfone applied 2 WAP caused up to 25% sesame injury (stunting) but did not result in a yield reduction. Quizalofop-P caused slight injury (<5%) and no reduction in yield.